Enhancing Sustainability Performance through Digital Capability: A Dynamic Capability Perspective in Indonesian National Oil and Gas Companies - Muhammad Sadikin; Yolanda Masnita Siagian; Tiara Puspa; Lucy Warsindah (Asian Journal of Social and Humanities, 2026)
This research aims to analyze the role of e-Leadership Capability, Dynamic Digital Workplace Policy, and Digital Culture in shaping the Sustainability Performance of Organization, with Quality Management as the mediating variable and Social Dynamism as the moderation variable, in the context of national oil and gas companies in Indonesia. This research uses a quantitative approach with the Structural Equation Modeling (SEM) method. Data was collected from 210 respondents representing various levels of the organization, ranging from Junior Analyst to Vice President (VP) levels, spread across various operational areas of national oil and gas companies in Indonesia. The results show that e-Leadership Capability has a positive and significant influence directly on Sustainability Performance, which confirms the crucial role of digital leadership in driving sustainable business achievements. In contrast, Dynamic Digital Workplace Policy and Digital Culture did not show a significant direct influence on sustainability performance. However, Dynamic Digital Workplace Policy and Digital Culture have proven to have a positive and significant effect on Quality Management, which further contributes strongly to the Sustainability Performance of Organization. The results of the mediation analysis showed that Quality Management mediated the influence of Dynamic Digital Workplace Policy and Digital Culture on the Sustainability Performance of Organization, while the mediating role between e-Leadership Capability and sustainability performance was not proven to be significant. In addition, Social Dynamism significantly moderates the relationship between Quality Management and Sustainability Performance of Organization, suggesting that social dynamics and stakeholder pressures strengthen the relationship between quality practices and sustainability achievements.